Identifying key components for a psychological intervention for people with vitiligo – a quantitative and qualitative study in the United Kingdom using web‐based questionnaires of people with vitiligo and healthcare professionals. (13th August 2018) - Ahmed, A.; Steed, L.; Burden‐Teh, E.; Shah, R.; Sanyal, S.; Tour, S.; Dowey, S.; Whitton, M.; Batchelor, J.M.; Bewley, A.P.
Abstract: Background: Psychological interventions are recommended as part of routine management of vitiligo. However, the development and effectiveness of such interventions have been rarely addressed. This study aimed to identify key components for a psychological intervention for people with vitiligo. This is the first time perspectives of people with vitiligo, and healthcare professionals (HCPs) have been directly explored to inform intervention content and delivery. Objectives: To identify 1. which psychological difficulties are highlighted that can be targeted by an intervention; 2. what is important in terms of intervention content and delivery. Methods: Web‐based questionnaires containing both quantitative and qualitative items were completed by people with vitiligo and HCPs. Questionnaires collected data from people with vitiligo on demographics, clinical features, psychological difficulties and priority areas for psychological interventions, including ideas on delivery and content. HCPs questionnaires collected data on psychological difficulties reported, use of psychological interventions and suitability within health services. Quantitative data were analysed using descriptive statistics, and qualitative data utilized thematic framework analysis. Results: A total of 100 people with vitiligo (66% female, 92% Caucasian) and 39 HCPs (54% dermatologists) participated. Key areas of difficulty were the impact of vitiligo, coping, issues with appearance/body image and the sun, and medical interactions. Vitiligo on sensitive sites was associated with more psychological impact. Interventions directed at increasing acceptance, confidence and self‐esteem, as well as managing embarrassment, were important. These issues could be managed through interventions such as cognitive behavioural therapy, mindfulness and acceptance and commitment therapy. Both people with vitiligo and HCPs favoured individual interventions. Conclusion: Vitiligo has significant impact, requiring ongoing psychosocial support. There is a strong need for a psychoeducational intervention with focus on acceptance and managing social impact. The results of this study are the first steps to informing the development of a patient‐centred psychological intervention. Abstract : Linked article: This article is commented on by A. Taïeb et al., pp. 2053–2054 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15297